Absence of transformation of beta-muricholic acid by human microflora implanted in the digestive tracts of germfree male rats. - Sacquet, E C (1984)
Germfree rats biosynthetize cholic and beta-muricholic acids. The latter does not exist in humans. Germfree rats were given human fecal suspensions. These rats degraded cholic acid into deoxycholic acid but failed to metabolize beta-muricholic acid.